PERAN GANDA PEREMPUAN DALAM MENINGKATKAN PENDAPATAN KELUARGA DI DESA SUMGAI DERAS KECAMATAM TELUK PAKEDAI KABUPATEN KUBU RAYA - B1024141026, Daniel Giovanni B1024141026 Daniel (Jurnal Manajemen Update, 2019)
ABSTRACTFor sustainability of the; company, business should be more customers oriented than profit oriented. In determining and selecting a product, customer shave their own trusted brand. When the customers trust with the brand, they will decide to purchase the products. For this research, there are several factors that affect the brand trust and purchase decision. This research is a survey research that is conducted to understand the causal relationships between variables with the use of questionnaire as the instrument to obtain data. The questionnaire is distributed to 100 sample who fulfill the requirements. The sample of this research is consumers in Pontianak who are above 17 years old and already use or buy Honda motorcycyle. In this research, the data analysis method used is Structural Equation Model Partial Least Square (SEMPLS) method. To conduct analysis using PLS method, this research is using smartPLS 3.0 software. The hypothesis of the research is H1: Product Innovation has positive influence on the Brand Trust of HondaÂ Â  Motorcycle in Pontianak, H2: Advertising Creativity has positive influence on Brand Trust of Honda Motorcycle in Pontianak, H3: Corporateâ€™s Images has positive influence on Brand Trust of Honda Motorcycle in Pontianak, H4: Product Innovation has positive influence on the Purchasing Decision of HondaÂ Â  Motorcycle in Pontianak, H5: Advertising Creativity has positive influence on Purchasing Decision of HondaÂ Â  Motorcycles in Pontianak, H6: Corporateâ€™s Images has positive influence on Purchasing Decision of Honda Motorcycle in Pontianak, H7: Brand Trust has positive influence on Purchasing Decision of Honda Motorcycle in Pontianak. Â The result of this research shows that H1, H3, H3, H6, and H7 are accepted but H4 and H5 are rejected.Key word: Product Innovation, Advertising Creativity, Corporate Image, Brand Trust, Purchasing DecisionÂ REFFERENCESÂ Kotler, Philip dan Keller, K. L. (2006). Marketing Management. Pearson Education Inc.Kuo, H.C. & Nakhata, C. (2016). "Price promotions and products with low consumer ratings", Journal of Consumer Marketing, Vol. 33 No. 7, pp. 517-527.Lau, Geok Then and Sook Han Lee. 1999. Consumers Trust in a Brand and the Link to Brand loyalty, Journal of Market Focused management.Lee, Monle dan Johnson Carla. 2004. Prinsip-Prinsip Pokok Periklanan Dalam Perspektif Global. Prenada Media. Jakarta.Lau, K.C. & Phau, I. (2007). â€œExtending symbolic brands using their personality: examining antecedents and implications towards brand image fit and brand dilutionâ€, Psychology and Marketing, Vol. 24 No. 5, pp. 421-444. â€¨Monroe, K.B. (2002). Pricing: Making Profitable Decisions, 3rd ed., McGraw-Hill, New York, NY. â€¨Lukas, Bryan A., and O.C. Ferrel., 2000. â€œThe Effect of Market Orientation on Product Innovationâ€. Journal of The Academy Marketing Science.Â No. 2Â Vol. 28 p. 239-247.Morgan, R.M. & Hunt, S.D. (1994). â€œThe commitment-trust theory of relationship marketingâ€, Journal of Marketing, Vol. 58 No. 3, pp. 20- 38.Mowen, John C. (2001). Perilaku Konsumen (edisi 5). Jakarta : Erlangga. Jilid 2 Morgan, RM and Hunt, S.D, 1994, The Commitment-Trust Theory of RelationshipNilsson, L., Johnson, M.D. & Gustafsson, A. (2001). â€œThe impact of quality practices on customer satisfaction and business results: product versus service organizationsâ€, Journal of Quality Management, Vol. 6 No. 1, pp. 5-27.Oliver, Richard. L., 1999. Satisfaction. A Behavioral Perspective on The Customer. First Edition. McGraw-Hill Companies, Inc. New York.Palilati., 2004., â€œPengaruh Tingkat Kepuasan terhadap Loyalitas Nasabah Tabungan Perbankan di Wilayah Bugisâ€, Jurnal Ilmu-Ilmu Sosial, pp. 65- 74.Robbins, Stephen P. (1994). Teori Organisasi Struktur, Desain dan Aplikasi. Prentice Hall International, Inc., San Diego.Rogers, E. M., & Shoemaker, F. F. (1983). Diffusion of innovation: A cross cultural approach. New York.